THE EFFECT OF DIFFERENT MEAT SHOP ON MEAT PHYSICAL CHARACTERISTICS AND BACTERIA POPULATION - Dewi, S.H.C.; Prihharsanti, A.H.T. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
An experiment was conducted to study the effect of different meat shops on meat physicalcharacteristics and bacteria population. Sixteen PO carcasses were used in the experiment which wasarranged in a completely randomized design with 4 treatments of different meat shops (traditionalmarket, meat shop, supermarket and slaughter house). Parameters measured were meat pH, waterholding capacity, cooking loss and bacterial total count. The result showed that the average of pH was5.25- 6.03; water holding capacity was 17.07-38.87%; cooking loss was 33.15-48.20 and bacterial totalcount was 1.48x106-10.75x106 CFU/g. It was concluded that bacterial total count in slaughter house andspecial market (meat shop and supermarket) were less than those in traditional market.